Penerapan Brevet Pada Lembaga Pendidikan: Studi Regulasi dan Kepatuhan - Anisa; Farida Ariyani; Nehemia Manurung; Putri Septianti; M Syahputra; Harry Soeratin (Jurnal Literasi Akuntansi, 2025)
Purpose: This study aims to analyze the application of tax brevet in higher education institutions in Indonesia, focusing on regulatory compliance and the impact on fiscal efficiency and financial governance. It seeks to evaluate the gap between existing tax regulations and practical needs, as well as the role of tax brevet in enhancing human resource competence and institutional performance. Method: The research employs a literature study approach, analyzing various written sources such as tax regulations, academic journals, and related research findings. The population includes higher education institutions in Indonesia, with a focus on their tax compliance practices and human resource capabilities. The sample consists of documented cases and regulatory frameworks pertinent to the topic. Finding: The study reveals that while tax brevet can significantly improve tax compliance and fiscal efficiency in higher education institutions, there is no explicit regulation mandating the employment of brevet-certified staff. Institutions with brevet-certified personnel demonstrate better fiscal performance and governance. However, reliance on external consultants remains prevalent due to gaps in internal capacity. Novelty: This research contributes to the limited literature on tax brevet in the education sector by highlighting its strategic role in financial governance. It proposes the integration of tax brevet into academic curricula and internal human resource development as a novel approach to addressing compliance challenges. Keywords: Tax brevet, higher education, tax compliance, financial governance, regulatory gap.